Socio-demographic risk factors of pulmonary tuberculosis: a case-control study in Yobe State, Nigeria - Yannabe, Mustapha M.; Abdul Rahman, Hejar; Kadir @ Shahar, Hayati; Hammangabd, Ahmad (Community Health Society Malaysia, 2015)
Background: There are many socio-demographic risk factors for pulmonary tuberculosis (PTB), however there are limited studies done in Yobe.